PENGARUH KOMPENSASI DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA KARYAWAN PT. JUI SHIN - Suryanto dan Jeri Andrian Ridwan (Fakultas Ekonomi Universitas Borobudur, 2015)
This study aims to determine the effect of Compensation and Job Characteristics on Employee Satisfaction at PT. ZHU SHINThe data used in this study is primeryang data collected from the results of questionnaires distributed and filled by employees of PT. ZHU SHIN on September 20, 2014 concerning compensation, job characteristics and employee satisfaction PT. ZHU SHIN.Metode data processing using Multiple Linear Regression analysis method with the help of SPSS version 19.0 software analysis tool. for Linux and Windows OS. The statistical test in this research use Multiple Linear Regression Test.The results showed that simultaneously variable Compensation, and Job Characteristics have a significant effect on Employee Satisfaction with the value of 85% which means both variables X affecting 85% of variable Y with a significant number of 0.000 <0.05 that means 25% explained by other variables outside research. The results of multiple linear regression research partially also shows the number 0.367 on the variable Compensation tehadap Employee Satisfaction and the number 0.380 on Job Characteristics of Employee Job Satisfaction that indicates the relationship is strong. Keywords: Compensation, Job Characteristics, Employee Job Satisfaction